2016
DOI: 10.4103/0366-6999.178960
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Adult/Adolescent Atopic Dermatitis and Chinese Criteria for Atopic Dermatitis

Abstract: Background:Atopic dermatitis (AD) is an inflammatory skin disease characterized by chronic recurrent dermatitis with profound itching. Most patients have personal and/or family history of atopic diseases. Several criteria have been proposed for the diagnosis of AD. Although the clinical features of childhood AD have been widely studied, there has been less large-scale study on adult/adolescent AD. The aim of this study was to investigate the clinical features of adult/adolescent patients with chronic symmetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 30 publications
0
71
0
2
Order By: Relevance
“…In addition, the awareness of AD by dermatologists and patients may also contribute to this phenomenon. In China, the symmetrical eczematous dermatitis tends to be diagnosed as eczema in the past decades, indicating an overdiagnosed eczema and underdiagnosed AD [7]. Until recent years, we began to pay attention to AD and have improved the accuracy of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the awareness of AD by dermatologists and patients may also contribute to this phenomenon. In China, the symmetrical eczematous dermatitis tends to be diagnosed as eczema in the past decades, indicating an overdiagnosed eczema and underdiagnosed AD [7]. Until recent years, we began to pay attention to AD and have improved the accuracy of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, few studies have paid attention to AD patients of all ages, despite the fact that the occurrence of AD among adults has been shown to significantly affect socioeconomic conditions in both Asian and Western countries [6]. A recent survey has investigated clinical features of adult/adolescent (12 years and over) AD [7], but the epidemiology of AD at all ages in China is yet to be elucidated. Therefore, the purpose of the current study is to determine the actual prevalence and clinical features of AD at all ages in outpatients with dermatitis and eczema across large tertiary hospitals in China.…”
Section: Introductionmentioning
confidence: 99%
“…Chinese diagnostic criteria specific for adult/adolescent AD have been proposed because adult‐onset AD is common within the Chinese population . The criteria require a patient to have symmetrical eczema for more than 6 months and one or more of the following: a personal or family history of atopic disease, elevated serum immunoglobulin (Ig)E levels, positive allergen‐specific IgE or eosinophilia …”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…In the recent years, in an effort to address this critical issue, a group of Chinese dermatologists lead by Prof. Yao from Jiao Tong University in Shanghai have published a series of studies dealing with the appropriateness of the classical diagnostic criteria such as those of Hanifin and Rajka and the UK working party for the diagnosis of AD in the Chinese paediatric population . In a first approach and previous publications, this group clearly showed that the stringent application of the Hanifin and Rajka criteria in Chinese children leads to a significant underestimation of the diagnosis of AD in this population when compared to the results obtained by clinically experienced dermatologists .…”
mentioning
confidence: 99%